2003
DOI: 10.1073/pnas.1037608100
|View full text |Cite
|
Sign up to set email alerts
|

The BglF sensor recruits the BglG transcription regulator to the membrane and releases it on stimulation

Abstract: The Escherichia coli BglF protein is a sugar-sensor that controls the activity of the transcriptional antiterminator BglG by reversibly phosphorylating it, depending on ␤-glucoside availability. BglF is a membrane-bound protein, whereas BglG is a soluble protein, and they are both present in the cell in minute amounts. How do BglF and BglG find each other to initiate signal transduction efficiently? Using bacterial two-hybrid systems and the Far-Western technique, we demonstrated unequivocally that BglG binds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 44 publications
(46 reference statements)
4
47
0
5
Order By: Relevance
“…25 Notably, BglG forms a precomplex with BglF at the membrane in the absence of the stimulating sugar. 17 It is very tempting to suggest that targeting of operon transcripts, which usually code for protein products that operate in the same pathway, is a universal mechanism that facilitates assembly of these products into complexes. Notably, when bglG is transcribed without bglF, its transcripts localize to the poles, 25 where the BglG protein forms a complex with the general PTS proteins after it is released from the membrane pre-complex upon sugar stimulation.…”
Section: Localization Of Bacterial Proteins Via Mrna Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Notably, BglG forms a precomplex with BglF at the membrane in the absence of the stimulating sugar. 17 It is very tempting to suggest that targeting of operon transcripts, which usually code for protein products that operate in the same pathway, is a universal mechanism that facilitates assembly of these products into complexes. Notably, when bglG is transcribed without bglF, its transcripts localize to the poles, 25 where the BglG protein forms a complex with the general PTS proteins after it is released from the membrane pre-complex upon sugar stimulation.…”
Section: Localization Of Bacterial Proteins Via Mrna Targetingmentioning
confidence: 99%
“…We showed that localization of the BglG transcription factor, which enables expression of a PTS sugar utilization operon, bgl, is determined by its consecutive interaction with different PTS components, i.e., with the PTS sugar permease BglF, which localizes around the cell circumference, and with the general PTS proteins at the poles. 12,17 Hence, upon sugar stimulation, BglG migrates from the cell periphery to the cytoplasm through the poles (Fig. 1).…”
Section: Spatial Organization Of Bacterial Signaling Systemsmentioning
confidence: 99%
“…Penicillinbinding proteins involved in cell wall synthesis have also been shown to localize in several patterns, including to division septa and discrete foci along the long axis of the cell, reflecting the role of these proteins in specific stages of cell wall synthesis (Scheffers et al, 2004). However, analysis of the localization of the E. coli Sec protein secretion machinery, BglF sugar sensor and B. subtilis phage w29 DNA replication protein p16.7 indicates that these proteins are homogeneously distributed around the cytoplasmic membrane, with no reported preference for cell poles or other observable domains (Brandon et al, 2003;Lopian et al, 2003;Meijer et al, 2001). Certainly, the images presented in these papers indicate that the localization pattern of these proteins creates a clear outline of the cytoplasmic membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in the absence of ␤-glucoside, BglG exists in the cell as a phosphorylated inactive monomer, whereas in the presence of the sugar in the growth medium, BglG exists as an active non-phosphorylated dimer. We have recently shown that in the absence of the stimulating sugar, BglF recruits BglG to the membrane, releasing it to the cytoplasm upon the addition of ␤-glucoside (7).…”
mentioning
confidence: 99%